Djibouti : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Djibouti. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2020)
The government has in recent years implemented large-scale investments to develop transport and logistics infrastructures. Combined with business climate reforms, this development strategy has fueled strong growth and positioned Djibouti well to become a regional trade and logistics hub. However, it has come at the cost of rising debt vulnerabilities, and fiscal revenues have lagged due to large tax expenditure. Despite some progress on social indicators, unemployment and poverty remain high.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet